Hypoglycemic and hypolipidemic activities of Arabic and Indian origin Salvadora persica root extract on diabetic rats with histopathology of their pancreas - Khan, Maria; Ali, Mohammad; Ali, Abuzer; Mir, S.R. (International Journal of Health Sciences, 2014)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA <![endif]–> Objective: To evaluate hypoglycemic and hypolipidemic effects of Salvadora persica aqueous extracts on streptozotocin-induced diabetic rats by measuring fasting blood glucose levels, lipid profiles and histopathological analysis of pancreas. Materials and Methods: Experimental Diabetes was induced by single intraperitoneal injection of streptozotocin (60 mg/kg) to albino Wistar rats. Salvadora persica extracts were administered orally at 250 and 500 mg/kg dose levels for 21 days. Glucose tolerance test (GTT) was performed on 16 h fasted rats and changes in blood glucose levels, total cholesterol, triglycerides, low-density lipoprotein (LDL), very low density lipoprotein (VLDL), high density lipoprotein (HDL) and histopathology of pancreas were performed. Results:At a dose level of 500 mg/kg, blood glucose 85.25 Â± 13.20 mg/dl, total cholesterol (TC) 114.57 Â± 15.81(mg/dl), triglycerides (TG) 75.40 Â± 16.47(mg/dl), LDL 42.63 Â± 13.17(mg/dl), VLDL 22.78 Â± 1.88(mg/dl), and elevation of HDL 44.88 Â± 11.61(mg/dl) were found in comparison with diabetic control on 28th day by Arabic origin Salvadora persica. It also accelerated the regeneration of Î²-cells in experimental animalâ€™s pancreas to 32.6 Â± 2.4 compared to diabetic control animalâ€™s pancreas of 8.1 Â± 0.5 at the end of 28th day. Conclusion: This study confirmed that Arabic Salvadora persica aqueous extracts at 500 mg/kg dose level, in comparison to other extracts (Indian Salvadora persica, 250 and 500 mg/kg, Arabic Salvadora persica 250 mg/kg) possessed significant hypoglycemic and hypolipidemic activities and regenerated pancreatic Î²-cells in streptozotocin treated diabetic rats. Key words: Salvadora persica, geo-comparison, antidiabetic activity, hypoglycemic activity, serum lipid profile, glucose tolerance test, histopathology, pancreatic Î²-cells, <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>